The conference on the future of Europe between form of state and form of government - Lucarelli, Alberto (Diritto Pubblico Europeo - Rassegna online, 2020)
<span style="background-color: #ffffff; color: #000000; font-family: " noto sans",arial,helvetica,sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">With regard to the Conference on the Future of Europe (2020-2022), on February 14, Italy presented a document entitled “Italian Non-Paper for the Conference on Europe”. The document consists of three paragraphs: 1 Introduction; 2. Bolstering the European democratic space, promoting a better functioning of the EU; 3. Fine tuning policies - Promoting a thorough debate on EU priorities.